Guru Nanak's Vision of God as a Model for Christian Ecumenism - Gaskill, Alonzo L. (Journal of ecumenical studies, 2017)
The article talks about the founder of Sikhism, Guru Nanak, and how his vision of a single God can be a model for Christian Ecumenism. Topics discussed include the concept of the Trinity in Christian denominations, the oneness of the three Persons or the individuality of the three as per the Trinity, and the author's view that the deciding factor in one's Christianity should be his belief that salvation is in and through the atoning blood of the Lord Jesus Christ.